TOTAL QUALITY MANAGEMENT ANALYSIS OF SURABAYA SINGLE WINDOW ALFA WEBSITE USE TO OPTIMIZE PUBLIC SERVICE QUALITY IN SURABAYA - Herliana Rusmalinda Zainia; Farij Ibadil Maula (Jurnal Pendidikan Administrasi Perkantoran (JPAP), 2026)
Phenomenon/Issue: This study was motivated by the gap between the availability of the Surabaya Single Window (SSW) Alfa digital service and its use  by the community in Lidah Wetan Village. Purpose: This study aims to examine the process of information dissemination and the factors contributing to information gaps related to the SSW Alfa website. It also analyzes the level of community utilization of the platform for administrative services in Lidah Wetan Village and identifies managerial obstacles in optimizing the quality of public services through SSW Alfa. Novelty: The novelty of this study lies in its analysis of the implementation of SSW Alfa from a Total Quality Management (TQM) perspective at the sub-district level. Unlike previous studies that primarily focus on the outcomes of digital services, this research also examines implementation management, the socialization process, service utilization, and managerial constraints in optimizing service quality. Research Methods: This study used a descriptive qualitative approach with interview, observation, and documentation techniques, and is analyzed through the stages of data reduction, data presentation, and conclusion drawing. Results: The results show that SSW Alfa has provided convenience and efficiency in licensing services. However, there are still obstacles in the form of uneven socialization, low digital literacy among some members of the community, and the need to simplify the menu display. From a TQM perspective, the implementation has reflected continuous improvement and total employee involvement as well as managerial efforts, although the focus on customers and obstacles still occur in optimizing socialization and strengthening digital literacy still needs to be improved. Research Contributions: This study contributes to a deeper understanding of the implementation of digital-based public services through the SSW Alfa website from a TQM-based quality management perspective. It also provides empirical insights into the importance of adaptive socialization strategies, improving public digital literacy, and strengthening the capacity of government officials to support the optimization of digital public services.